Kuat Tekan Dan Porositas Beton Geopolimer Hybrid Faba Dengan Penambahan Semen PCC Di Air Gambut - Ikrammullah, Muhammad; Olivia, Monita; Wibisono, Gunawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Geopolymer hybrid concrete is formed from materials containing alumina and activated silica using an alkali activator with the addition of portland cement to produce heat of hydration, so as geopolymer concrete treatment can be carried out at room temperature. The purpose of this research to knowing durability of geopolymer hybrid FABA concrete with the addition of PCC after exposed to peat water for 0, 7, and 28 days. Control concrete with a design quality of 20 MPa. The activator solution used NaOH with molarty 12M and Na2SiO3 with a modulus ratio (Ms) of 2.5. The percentage added of PCC cement is 15% by weight of FABA. Results of the test showed that the compressive strength of PCC concrete increased 8.82%, while geopolymer hybrid concrete increased 6.88% until the age of 28 days cured in peat water. Moreover, the porosity of PCC concrete of PCC concrete decreased 3.01%, while geopolymer hybrid an increase 6.08% until the age of 28 days cured in peat water.Keyword: peat water, geopolymer hybrid, concrete, compressive strength, porosity, fly ash and bottom ash.